Maternal Early Warning Scores (MEWS): Development of a Nigerian National Maternal Early Warning Scores (MEWS) Version - ISEMEDE, Asekhame Oise; BECKLEY, Sarah O (International Journal of Innovative Research in Medical Science, 2020)
Maternal Early Warning Scores (MEWS) is an acute maternity illness severity scoring and escalation trigger system. Background: The use of the MEWS in Nigerian obstetric practice is rare but with the strong desire for its use reported and the increasing number of international partnerships with clinicians in Nigeria for the introduction of this tool, the use of multiple versions of MEWS into the Nigerian clinical practice has been recognised as a potential patient safety risk best managed through the development of a Nigerian national MEWS version. Aims: We set out to explore the development of a Nigerian National MEWS version that would make an acceptable fit for the Nigerian acute obstetric care environment to be used by all clinicians involved in acute obstetric care in Nigeria. Methods: The United Kingdom MOEWS was used as the baseline (template); following planned training on MEWS using the above template, surveys of experts at these meetings on the suitability (for Nigeria) and necessity for modifications of the template was done using survey monkey and paper-based questionnaires. Results: One hundred and forty one experts responded out of two hundred requests (70.5%), one hundred and twenty five (88.6%) opted for modifications of the template. Of these, one hundred and three (82.4%) favoured the addition of a parameter directly related to pre-eclampsia. Conclusion: A modification of the UK MOEWS by the addition of another parameter related to pre-eclampsia was favoured by the majority of experts in this study for the development of a Nigerian national MEWS.